Peptides of the liver stage antigen-1 (LSA-1) of Plasmodium falciparum bind to human hepatocytes (2003)
Synthetic peptides from the liver stage antigen-1 (LSA-1) antigen sequence were used in HepG2 cell and erythrocyte binding assays to identify regiones thar could be involuved in parasite invesion. LSA-1 protein peptides 20630 ( 21 INGKIIKNSEKDEIIKSNLRY 40), 20637 (157 KEKLQGQQSDSEQERRAY 173), 20638 (174 KEKLQEQQSDLEQERLA 190) and 20639 (191KEKLQEQQSDLEQERRAY 207) had high binding activity in HepG2 assays. Were located in immunogenic regions; peptides cell binding was saturable. Peptide 20630 bound specifically to 48 kDa HepG2 membrane surface protein. LSA-1 peptides 20630 (21 INGKIIKNSEKDEIIKSNLRY 40) and 20633 (81 DKELTMSNVKNVSQTNFSLY 100) showed specific erythrocyte binding activity and inhibited merozoite invasion of erythrocytes in vitro. A monkey serum prepared against LSA-1 20630 peptide analog (CGINGKNIKNAEKPMIIKSNLRGC) inhibited merozoite invasion in vitro. The data suggest LSA-1 “High Activity Binding Peptides” could play a possible role in hepatic cell invasion as well as merozoite invasion of erythrocytes.